'Strict', yet ineffective: legal protection of breeding sites and resting places fails with the Siberian flying squirrel. (30th July 2014) - Jokinen, M.; Mäkeläinen, S.; Ovaskainen, O.
Abstract Lack of evaluation of the effectiveness of conservation practices as well as the challenge of converting scientific knowledge into conservation legislation and policy are persistent problems in conservation biology. European Union's Habitats Directive obliges member states to establish and implement a system of strict protection of animal species listed in Annex IV(a). This implies for example, that the deterioration or destruction of breeding sites or resting places of these species is prohibited. Here, we evaluate the effectiveness of the protection procedure aimed at conserving sites occupied by the Siberian flying squirrel Pteromys volans from destruction as a consequence of timber harvesting. We assess the potential effectiveness of the protection procedure by combining survey data with a simulation approach, showing that c. 97% of forests occupied by the species are harvested without authorization, as a result of inadequate information on the occurrence of the species. We assess forest structure around our study sites, visited both at the time of the protection decision and 1–6 years later, and show that clear‐cut areas within 150 m of breeding sites and resting places substantially increase the risk of abandonment. In spite of this, typically only areas of radius 10–30 m are protected from logging. As the territory is abandoned in c. 50% of the cases in spite of protection of breeding sites and resting places, the total effectiveness of this conservation measure is only c. 1.5%. Therefore, the current protection measure is inadequate against the threats that forestry poses for the species in Finland, and the focus should be turned to habitat and population level solutions. We suggest that researchers and decision‐makers should pay more attention to the overall effectiveness of different conservation measures, as this information is crucial for developing effective conservation policies.